New Public Management and the new professionalism in education: Framing the issue - Gary Anderson; Kathryn Herr (Education Policy Analysis Archives, 2015)
This article provides an introductory frame for this special issue dedicated to New Public Management and the New Professional Educator. We will intoduce the five  articles and how they analyze the characteristics of NPM and this emerging new professional as well as forms of educator resistance and advocacy.